Simulations of catalytic ozone decomposition reaction in fluidized bed [electronic resource] - Muhamad Nor Ikhwan Zaid, 1983- (2013)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2013